Analisis Permintaan Transportasi Laut Berdasarkan Data Historis Keberangkatan Penumpang di Jayapura - Prawardani, Dinda Sekar Selni; Pabinte, Marcelia Eliezer (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2025)
Indonesia, an archipelago of over 17,000 islands, relies heavily on maritime transportation for inter-regional connectivity, given that its waters constitute over 62% of its total area. Situated on a strategic global trade route, Indonesia is developing its maritime infrastructure through initiatives like the "Tol Laut" program to enhance logistical efficiency and economic growth. Jayapura, with its vital port, plays a significant role in the national sea transportation system, connecting Papua and other Indonesian regions. Data from the Papua Province Statistics Agency (BPS) reveals a substantial increase in passenger traffic at Jayapura Port in December 2024, with a 24.15% rise in departures (23,591). This surge aligns with predictions of peak travel during the Christmas and New Year holidays. Unlike previous studies focusing on predictive modeling, this research employs a descriptive analysis of historical passenger at Jayapura Port to identify demand trends influenced by seasonal factors, specifically holidays and religious celebrations, without considering economic or demographic variables. Based on what writer do in this topic, the results of data that has been made in the Microsoft Excel application using data from (Central Statistics Agency/BPS) are that the most passengers are in December-January (holidays) and also mid-year holidays. The highest MoM occurs between November and December, while the highest YoY is in the comparison of December 2021 with December 2022, namely (68.99%) due to the transition after Covid-19. Until now, the increase in the use of sea transportation has continued to increase, especially during the seasonal period. So with this research, it is hoped that it can help provide information and policies to improve services during periods of high demand.